Rekontruksi Sistem Pertanggungjawaban Pidana Korporasi Atas Kejahatan Terhadap Lingkungan Hidup Perspektif Hukum Progresif - Pravifjayanto, Mochammad Rafi (Jurnal Hukum & Pembangunan, 2025)
The environment as a place for humans to live certainly needs to be preserved and protected for its existence. In the context of statehood, the Indonesian Constitution guarantees the constitutional right of citizens to a clean environment. Thus, regulations as the face of the Indonesian constitution must not contradict the constitution. Juridically, Indonesia regulates life protection in Law Number 32 of 2009 concerning the Protection of Environmental Management. However, in its implementation, there are many violations of environmental management which in fact are carried out by corporations to obtain economic benefits. This study aims to analyze the corporate criminal responsibility system as an actor of crime in the environmental sector, and try to formulate criminal norms for corporations that can meet the principles of justice for the community. By using the normatic method with a Critical Legal Studies approach, conceptual, and legislation will produce new norms related to an equitable corporate accountability system.